Las tics y su incidencia en los procesos gerenciales para la comunicación efectiva en el colegio Machala, periodo lectivo 2016 – 2017. - Jácome Aguilar, Emilio José (2017)
Starting from a communicational approach at the managerial level, the univocal relationship between the sender and receiver of the decoding of a message is maintained. The multiple structural conjunctures of the knowledge society and the information society motivate a viable scaffolding of information in order to restructure the outdated and up-to-date mental schemas of the managers of an EI. Taking into account the Technocratic paradigm, the processes at the managerial level are streamlined in a conciliatory proposal that emerges from an imperative need for institutional advancement, based on theoretical constructs of innovation and technology. Searching for societies with birth with the immediacy of information provides opportunities that precede epistemological assumptions rooted in science.